A process evaluation model for patient education programs for pregnant smokers. (1st September 2000) - Windsor, Richard A; Whiteside, H Pennington; Solomon, Laura J; Prows, Susan L; Donatelle, Rebecca J; Cinciripini, Paul M; McIlvain, Helen E
Abstract : OBJECTIVE: To describe and apply a process evaluation model (PEM) for patient education programs for pregnant smokers. METHODS: The preparation of a process evaluation plan required each program to define its essential "new" patient assessment and intervention procedures for each episode (visit) of patient–staff contact. Following specification of these core implementation procedures (p) by each patient education program, the PEM, developed by the Smoke-Free Families (SFF) National Program Office, was applied. The PEM consists of five steps: (1) definition of the eligible patient sample (a); (2) documentation of patient exposure to each procedure (b); (3) computation of procedure exposure rate (b/a = c); (4) specification of a practice performance standard for each procedure (d); (5) computation of an implementation index (c/d = e) for each procedure. The aggregate of all indexes (e) divided by the number of procedures (Pn ) produced a program implementation index (PII = Σe/Pn ). PARTICIPANTS AND SETTINGS: Data from four SFF studies that represent different settings were used to illustrate the application of the PEM. RESULTS: All four projects encountered moderate to significant difficulty in program implementation. As the number and complexity of procedures increased, the implementation index decreased. From initial procedures that included patient recruitment, delivery of the intervention components, and conducting patient follow ups, a variety of problems were encountered and lessons learned. CONCLUSION: This process evaluation provided specific insight about the difficulty of routine delivery of any new methods into diverse maternity care setting. The importance of pilot testing all procedures is emphasised. The application of the PEM to monitor program progress is recommended and revisions to improve program delivery are suggested.